Precipitation Alters the Effects of Temperature on the Ecosystem Multifunctionality in Alpine Meadows - Ma, Yunhe; Tian, Lihua; Qu, Guangpeng; Li, Ruicheng; Wang, Weiwei; Zhao, Jingxue (Frontiers in Plant Science, 2022)
Precipitation and temperature are major controls on multiple ecosystem functions in alpine grasslands. However, there is scant evidence for the effects of temperature and precipitation changes on the ecosystem multifunctionality (EMF) in alpine meadows. In order to explore the interactive effects of temperature and precipitation changes on the EMF in alpine meadows, we transplanted meadow blocks reciprocally among three altitudes (4650 m, 4950 m and 5200 m) on the central Tibetan Plateau. Compared with the home sites, the EMF has a trend to increase or decrease when meadow blocks were downward transplanted (experimental warming) to the high-precipitation sites or low-precipitation sites, respectively. However, the experimental cooling (upward transplantation) consistently reduced the EMF regardless of the precipitation change. The increase of EMF under the experimental warming was closely related to the variation of both plant and soil functions, whereas the reduction of EMF under the cooling was highly correlated with the decrease of plant function. Our results highlight that climate warming effects on the EMF are greatly associated with precipitation changes in the water-limited alpine ecosystems.